Functionalization of β-cyclodextrin with a urea-based PSMA ligand and preliminary studies on targeting prostate cancer cells. (1st October 2022) - Imperio, Daniela; Grolla, Ambra A.; Moro, Marianna; Bortolotto, Valeria; Del Grosso, Erika; Genazzani, Armando A.; Panza, Luigi
Graphical abstract: Abstract: Targeted delivery of drugs into specific cancer cells is an effective way to enhance the efficacy and minimize the side effects of therapy. Prostate malignant cells overexpress the prostate-specific membrane antigen (PSMA), a membrane protein that may be a valid target for selective drug administration. To target prostate cancer cells, a β-cyclodextrin perfunctionalised with dipeptide-like urea arms, a well-established mimic of a selective ligand against PSMA, is herein reported, to develop a multivalent drug delivery and targeting system. Firstly, fluorescein was used to validate the system on cells that express high levels of PSMA (prostate tumoral cells, LNCap) or very low levels of PSMA (non-tumoral cells, Hek293T). Then, the antineoplastic agent doxorubicin complexed with β-cyclodextrin functionalized with PSMA-like ligand takes less time to induce cytotoxicity on LNCap cells compared to doxorubicin alone. This might represent a promising drug-delivery approach to selectively target prostate cancer cells.